STRENGTHENING THE ROLE OF UMKM (KnK KOFFEE RESOURCES) THROUGH SOCIALIZATION AND COMPLETION OF THE COMPOSITION OF FINANCIAL STATEMENTS AND TAX REPORTS (Study in the Home Industry Processing Coffee Beans Supply 75% Coffee Shops in Semarang) - Sari, Maylia Pramono; Suryarini, Trisni; Maftukhah, Ida (Universitas Negeri Semarang, 2019)
The activities of community services conducted by the Community Services Team of Universitas Negeri Semarang (PPM Unnes) with a target audience of micro small and medium enterprises (SMEs) in the city of Semarang, namely Knk Koffee Resources. The home industry of coffee processing is the stockist of 60 (supplier 75%) coffee shops in Semarang, the average incomes is 100 million per month. The purpose of the PPM activities to provide reinforcement to the PPM program partners by providing solutions to the problems faced. KnK Koffee Resources does not yet have a regular financial statement, relying solely on billing recap and sales receipt. Recognition from the owner that it is still difficult to make a good decision when relying solely on bookkeeping reports that have been owned. Therefore, this PPM activity is carried out in the form of socialization, training and mentoring with the provision of materials (lectures and simulation practices) related to the preparation of financial statements and tax reports. Expected to improve the knowledge and skills of owners and employees of the administration (bookkeepers and treasurer) in conducting financial management, financial and tax report preparation, increasing sales income and facilitating funding for business expansion. Semarang Mayor is very supportive, give positive appreciation and make the example of KnK Koffee Resources as a coffee processing home industry that has successfully penetrated business penetration, not dwell in the market of Semarang only. With the improvement of financial reporting system to KnK Koffee Resources triggers the creation of a young business ecosystem of startups in Semarang. Kegiatan pengabdian yang dilaksanakan oleh Tim Pengabdian Pada Masyarakat Universitas Negeri Semarang (PPM Unnes) dengan khalayak sasaran Usaha Mikro Kecil dan Menengah (UMKM) di Kota Semarang yaitu Knk Koffee Resources. Industri rumahan pengolahan kopi ini merupakan stockist dari 60 (penyuplai 75%) kedai kopi di Semarang, beromset rata rata 100jt per bulan. Tujuan dari kegiatan PPM untuk memberikan penguatan kepada mitra program PPM dengan memberikan bantuan solusi atas permasalahan yang dihadapi. KnK Koffee Resources belum memiliki laporan keuangan regular, hanya mengandalkan pada rekap billing dan nota hasil penjualan. Pengakuan dari pemilik bahwa masih sulit dilakukan pengambilan keputusan bila hanya mengandalkan pada laporan pembukuan yang selama ini dimilikinya. Oleh karena itu kegiatan PPM ini dilakukan dalam bentuk sosialisasi, pelatihan dan pendampingan dengan pemberian materi (ceramah dan praktik simulasi) terkait penyusunan laporan keuangan dan laporan pajak. Diharapkan dapat meningkatkan pengetahuan dan ketrampilan pemilik serta karyawan administrasi (pembuku dan bendahara) dalam melakukan pengelolaan keuangan, penyusunan laporan keuangan dan pajak, meningkatnya omset penjualan dan memudahkan pendanaan untuk ekspansi usaha. Walikota Semarang sangat mendukung, memberi apresiasi positif serta menjadikan contoh KnK Koffee Resources ini sebagai industri rumahan pengolahan kopi yang telah berhasil melakukan penetrasi bisnis keluar, tidak hanya berkutat di market Kota Semarang saja. Dengan pembenahan sistem pelaporan keuangan pada KnK Koffee Resources memicu terciptanya ekosistem bisnis rintisan anak muda di Kota Semarang yang lebih baik.